Análise dos efeitos da pandemia da COVID-19 na experiência cotidiana de profissionais e usuários de um CAPS AD III - Silva , Stéfhane Santana da (2024)
The World Health Organization (WHO) declared the beginning of the covid-19 pandemic in March 2020, constituting a health crisis of international importance, which affected the entire world population, causing several changes, imposing multiple challenges, especially in the scope of the health system, considering the overload of demands met during this period. Thus, this research aimed to analyze the effects of the covid-19 pandemic on the daily experience of professionals and users of a Psychosocial Care Center for Alcohol and Other Drugs III (CAPS AD III), establishing a relationship with the ongoing psychiatric reform process in the country. It is known that this process took place in parallel with the health reform movement that began in the 1970s, culminating in the construction of the Unified Health System (SUS), as well as in the expansion of the concept of health, based on comprehensive care, promoting the redirection of mental health care. Thus, with the implementation of public mental health policy, territorialized care is advocated, in freedom, with the promotion of autonomy and citizenship of people with mental disorders and as a result of the use of alcohol and other drugs, and who need to access the service. With that, it produces strategies, aiming at overcoming the biomedical model, and strengthening psychosocial care. In this sense, the study presents itself as a research of an applied nature, of the exploratory type, based on the inductive method and a qualitative approach to the data, using narrative interviews to carry out the collection. To help the analysis process, the content analysis method was applied, which is divided into three poles: pre-analysis, material exploration, and treatment of results, inference and interpretation. From the analysis of the results, it was observed that the pandemic had several effects on the daily lives of professionals and users, among them, the interruption of collective activities, reorganization of the service flow and access to the service, with the performance of screenings to verify signs and symptoms of covid-19, use of personal protective equipment in all consultations, reduction in the number of vacancies for 24-hour reception, reinforcement regarding the use of medications, loss of living spaces, and use of digital information and communication technologies for carrying out consultations, meetings and matrix support. Therefore, the need to build training processes through permanent education and popular health education was identified, aiming at the collective construction of coping strategies, and the participation of professionals, users and managers of the SUS. In addition, it is also considered important to establish spaces for evaluating the measures implemented during this period, according to the health situation and proximity or distance to the principles of psychiatric reform.